MLC 901 Decreases HSP-70, MMP-9, Cerebral Infarction Volume and Functional Outcome in Acute Ischemic Stroke Rat Model - Ilsa Hunaifi; Andi Kurnia Bintang; Jumraini Tammasse; Isra' Wahid; Mohammad Hatta; Andi Asadul Islam; Andi Alfian Zainuddin; Paulus Sugianto (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Acute ischemic stroke (AIS) is usually treated with thrombolysis, however the percentage of patients receiving this therapy is not quite low. Therefore, it is necessary to find alternative therapy using neuroprotective agent such as Moleac (MLC) 901. Heat shock proteins (HSP)-70 and matrix metalloproteinase (MMP)-9 are usually related to AIS due to the triggered stroke-induced physiological stress. However, the effect of MLC 901 on Hsp70 mRNA expression, HSP-70 and MMP-9 remains unclear. This study was conducted to determine the effect of MLC 901 on those three parameters in relation to cerebral infarction volume and functional outcomes in an AIS model.METHODS: Rats were induced with AIS using unilateral common carotid artery occlusion (UCAO) and received three different treatments: 43.2 mg/200 gBW MLC 901, 21.6 mg/200 gBW MLC 901, and sodium carboxymethyl cellulose (CMC-Na), that were administered orally for 14 days. HSP-70 and MMP-9 protein levels were assessed using enzyme-linked immunosorbent assay (ELISA), and Hsp70 mRNA expression was assessed using quantitative real-time polymerase chain reaction (qRT-PCR). Foot fault scores for evaluation functional outcome and infarction volume were assessed by ImageJ.RESULTS: AIS-induction increased HSP-70, MMP-9, and Hsp70 mRNA expression within 24-48 h. MMP-9, HSP-70 , and Hsp70 mRNA expression were reduced by MLC 901. MLC 901 at dose of 43.2 mg/200 gBW and 21.6 mg/200 gBW were effective in reducing these levels compared to the control. MLC 901 improved functional outcomes and decreased cerebral infarction volume. Moreover, a dosage of 43.2 mg/200 gBW was more effective in reducing Hsp70 mRNA expression and HSP-70, improving functional outcomes, and reducing cerebral infarction volume than a dosage of 21.6 mg/200 gBW, but not MMP-9 protein.CONCLUSION: MLC 901 effectively decreased Hsp70 mRNA expression, HSP-70 and MMP-9 protein levels, infarct volume, and functional outcomes. MLC 901 could be a potential therapeutic agent for AIS.KEYWORDS: MLC 901, HSP-70, MMP-9, acute ischemic stroke